أثر إدارة علاقات الزبائن إلكترونيا في الأداء التسويقي للبنوك الجزائرية - قريشي,شيماء; قريشي,محمد; مغزي لعرافي,راضية (University of Eloued جامعة الوادي, 2024)
ملخص: هدفت هذه الدراسة إلى التعرف على أثر إدارة علاقات الزبائن إلكترونيا على الأداء التسويقي للبنوك محل الدراسة، وتحديد مستوى توفر كل منهما، والتعرف أيضاً على طبيعة العلاقة والأثر بينهما، ولتحقيق ذلك تم تطوير استبانة وتوزيعها على عينة الدراسة البالغ حجمها (90) موظف وموظفة وهذا من خلال عدة زيارات ميدانية. استخدم في التحليل الإحصائي للبيانات عدة أساليب إحصائية منها: مقاييس الإحصاء الوصفي (المتوسط الحسابي، الإنحراف المعياري)، وتحليل الإنحدار البسط... الخ. توصلت الدراسة إلى عدة نتائج أهمها: مستوى توفر كل من إدارة علاقات الزبائن إلكترونيا والأداء التسويقي للبنوك محل الدراسة جاء مرتفعا وفقا لمقياس الدراسة، أيضا وجود أثر إيجابي لإدارة علاقات الزبائن إلكترونيا على الأداء التسويقي للبنوك محل الدراسة، إذ أن (%43.2) من التغيرات الحاصلة في الأداء التسويقي للبنوك محل الدراسة تفسرها إدارة علاقات الزبائن إلكترونيا. كما توصلت الدراسة إلى جملة من الاقتراحات أبرزها: على البنوك محل الدراسة الاستجابة بسرعة لطلبات الزبائن، وإتباع مبدأ التحسين المستمر في جميع تعاملاتها وعملياتها، وزيادة مبيعاتها بغية الحصول على حصة سوقية أكبر، هذا بالإضافة إلى تشجيع الموظفين على التعامل الجيد مع الزبائن. Abstract: The Focus of this study is to examine the impact of customer relationship management electronically on the marketing performance of the banks under study, and determine the level of availability of each of them, as well as identify the nature of the relationship and the impact between them. Achieving this, a questionnaire was developed and distributed to the study sample of (90) male and female employees through many field visits. Several statistical methods were used in the statistical analysis of the data, including: descriptive statistics measures (arithmetic mean, standard deviation), numerator regression analysis, etc. The study reached various results, the most important of which are: The level of availability of both customer relationship management electronically and the marketing performance of the banks under study was high. There was also a positive impact of customer relationship management electronically on the marketing performance of the banks under study, as (43.2%) of the changes occurred to the marketing performance of the banks under study is explained by customer relationship management electronically. Furthermore, the main suggestions drawn from this study are: The banks under study must respond quickly to customer requests, follow the principle of continuous improvement in all their dealings and operations, and increase their sales in order to obtain a larger market share, in addition to encouraging employees to deal well with customers.
دراسة تطبيقية في مجموعة من البنوك على مستوى ولاية بسكرة
Keywords: إدارة علاقات الزبائن إلكترونيا; أداء تسويقي; حصة سوقية; Electronic Customer Relationship Management; Marketing Performance; Market Share; Sales; Profitability; Customer Satisfaction